2021
DOI: 10.1001/jamaneurol.2021.0364
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery in Patients With Idiopathic Intracranial Hypertension—The Silver Bullet?

Abstract: popproj.html 9. Matthews KA, Xu W, Gaglioti AH, et al. Racial and ethnic estimates of Alzheimer's disease and related dementias in the United States (2015-2060) in adults aged Ն65 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, surgery did not have a greater effect on papilledema grade, visual function, or headache disability than CWM. 3 More specifically, there was no difference in visual acuity, contrast sensitivity, perimetric mean deviation, or optic nerve and the retinal nerve fiber layer. Given that loss of vision is the most severe complication in IIH, and headache is the principal symptom, not highlighting these supplementary data in either the initial or follow-up paper seems to be a crucial omission.…”
mentioning
confidence: 86%
“…However, surgery did not have a greater effect on papilledema grade, visual function, or headache disability than CWM. 3 More specifically, there was no difference in visual acuity, contrast sensitivity, perimetric mean deviation, or optic nerve and the retinal nerve fiber layer. Given that loss of vision is the most severe complication in IIH, and headache is the principal symptom, not highlighting these supplementary data in either the initial or follow-up paper seems to be a crucial omission.…”
mentioning
confidence: 86%
“…Persistent weight loss is a key strategy for mitigating the symptoms of intracranial hypertension and reducing the risk of complications associated with obesity. 140 , 141 , 142 Although the 2018 consensus guidelines on the management of IIH suggested that all patients with a BMI >30 kg/m 2 should prioritize weight management, they did not specify the amount of weight loss necessary to improve the disease or the most effective weight loss strategy. 6 The IIH:WT, involving 66 females with active IIH and a BMI of ≥35 kg/m 2 at five UK hospitals, showed that bariatric surgery was significantly more effective in reducing ICP than were community weight management programs.…”
Section: Treatmentmentioning
confidence: 99%
“…Some limitations are pointed out by Deb Friedman in an accompanying editorial(1). For instance, 14 (42.4%) participants randomized to the weight management arm never attended a Weight Watchers session, 2 participants withdrew from the study, and 2 participants underwent bariatric surgery on their own.…”
Section: Commentsmentioning
confidence: 99%